1999
DOI: 10.1002/stem.170286
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hematopoietic Activities of Human Bone Marrow and Umbilical Cord Blood CD34 Positive and Negative Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 37 publications
2
47
0
1
Order By: Relevance
“…Especially after transfer of CD34 + cells from UCB, the main cell lineage recovering in the NOD/SCID mice has been reported to be of B cells. [24][25][26][27][28][29] Similarly, we found that after relatively low doses of UCB CD34 + cells 81-95% of the engrafted cells were of B cell origin. At these doses only very low engraftment was found with BM or mPB CD34 + cells, not allowing reliable evaluation of specific cell lineages by flow cytometry.…”
Section: Discussionmentioning
confidence: 85%
“…Especially after transfer of CD34 + cells from UCB, the main cell lineage recovering in the NOD/SCID mice has been reported to be of B cells. [24][25][26][27][28][29] Similarly, we found that after relatively low doses of UCB CD34 + cells 81-95% of the engrafted cells were of B cell origin. At these doses only very low engraftment was found with BM or mPB CD34 + cells, not allowing reliable evaluation of specific cell lineages by flow cytometry.…”
Section: Discussionmentioning
confidence: 85%
“…Separation of these cells is particularly difficult not only because of the very low percentage of stem cells present but also because of variation in expression levels of the stem cell marker, CD34 (29,30). Preliminary results suggest that optimal magnetic labeling of CD34 1 cells from umbilical cord blood requires at least 15 ml/10 6 cells a-PE-MACS when the cells are saturated with a-CD34-PE (unpublished results).…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8][9][10][11]16 A number of clonal tracking studies using retro-or lenti-viral vector have shown that CB-derived CD34 þ cells are a heterogeneous population and contain ST-and LT-repopulating SRCs. 16,[18][19][20][21] Guenechea et al 18 revealed that the type of repopulation in NOD/SCID mice that receive transplants of retrovirally transduced CB-derived HSCs is generally oligoclonal with an extensive variability in the life span and proliferative capacity of individual SRCs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have revealed that the severe combined immunodeficiency (SCID)-repopulating cell (SRC) activity reside in CD34-positive (CD34 þ ) cell factions derived from bone marrow (BM), cord blood (CB), and peripheral blood. [1][2][3][4][5][6] Recently, we successfully identified human CB-derived CD34-negative (CD34 À ) SRCs with extensive lymphoid and myeloid repopulating ability using the intra-bone marrow injection (IBMI) method. 7 Functional studies revealed that these CD34 À SRCs have different HSC characteristics from earlier-reported CD34 þ SRCs.…”
Section: Introductionmentioning
confidence: 99%